Uso e cobertura do solo na capacidade potencial de armazenamento hídrico em microbacias - Noronha, Maísa de (2017)
The forest cover influences on runoff, supporting the best water precipitation infiltration of rainwater than other land-uses and, it has interfered positively on the water availability. This way, the land-cover changes, which are caused by the unplanned use of soil have caused problems as the reduction in the surface water flow. In this context, the objective of this study was the evaluation of the water-storage potential capacity in watersheds, aiming at comparing the runoff in function of its land-use/land-cover. It was verified the hydrology watersheds through the Curve Number method, highlighting the runoff coefficient (RC) parameter. The hydrology parameters were produced in three humidity conditions, defining the relation between the RC and real flow rates, that were collected during one hydrology year. The result was the flow variation depending on the rain, however, it happened with the land-uses influencing differently in the watersheds hydrology. Thus, there were differences in the water availability for the watersheds and, that one with the larger amount of forest cover area presented larger flow for all hydrology year. The land-use/land-cover influenced in the water-storage and in the runoff response-time. The highest RC value was observed, for the watershed with the highest forest cover area, in the follow conditions: drought and dry, average humidity and, soil moisture value close to field capacity. The second watershed, that has lower area cover by forest than the first. Likewise, its flow was function of the rain and, the land-use/land-cover had influenced directly in the water-storage and in the runoff response-time